2021
DOI: 10.31577/ahs-2021-0022.02.0036
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of soil water content differences after biochar application andits repeated application during 2020 growing season

Abstract: Soil water content is an important factor influencing crop yield quantity and quality. Extreme meteorological events are more frequent in our geographical conditions in last years and they affect soil water storage. Biochar is an organic material and one of its properties is soil water holding for a longer time. This is one of great benefits during non-precipitation days. Our study is focused on soil water content changes with biochar amendment in comparison to soil without biochar. In addition, we analyzed bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This was due to the fact that the additive particles filled the space between the soil particles and as a result, the water was filtered lower than unmodified soil (Bilardi et al, 2020). Also other authors observed impact of soil amendments (biochar) on K values in different soil (Toková et al, 2023;Vitková et al, 2019;Brockhoff et al, 2010;Uzoma et al, 2011). In the case of Slovak Silty clay soil, the opposite effect was observed.…”
Section: Saturated Hydraulic Conductivitymentioning
confidence: 97%
“…This was due to the fact that the additive particles filled the space between the soil particles and as a result, the water was filtered lower than unmodified soil (Bilardi et al, 2020). Also other authors observed impact of soil amendments (biochar) on K values in different soil (Toková et al, 2023;Vitková et al, 2019;Brockhoff et al, 2010;Uzoma et al, 2011). In the case of Slovak Silty clay soil, the opposite effect was observed.…”
Section: Saturated Hydraulic Conductivitymentioning
confidence: 97%
“…Coarse biochar particles increased intraporosity and fine biochar particles decreased hydraulic conductivity due to reduced macropores. Conversely, in loamy soils, biochar tends to reduce soil bulk density (Toková et al, 2020), increase soil porosity (Vitková et al, 2019), improve soil texture (Sun and Lu, 2014;Walters and White, 2018), and consequently increase K (Esmaeelnejad et al, 2017) and soil water content (Vitková et al, 2021). According to previous studies of the effect of biochar on fine textured clay soils, its positive effect is not clearly demonstrable (Castellini et al, 2015).…”
Section: Evaluation Of Biochar Application Impact On the Soilmentioning
confidence: 99%